Issues and trends in fashion education sustainability - Bedor, Abu; Sarimah, Sarimah; Arasinah, Kamis; Sharifah, Shafie; Ahmad Puad, Farah Najwa; Rahimah, Jamaluddin; Mohd Bekri, Rahim (2021)
United Nations (UN) has declared Sustainable Development Education (ESD) as an effort to achieve sustainable development goals (SDGs). Hence, it is encouraged that all parties globally, the government, the industry and education to implement a holistic and creative ESD approach to realize the goals of SDGs. ESD issues are also discussed in fashion education because the fashion industry is a contributor to environmental pollution. Thus, the values of sustainability in fashion education should be applied to students at an early stage so that students can understand different perspectives when faced with sustainability issues. In addition, students' attitudes and behaviour towards environmental issues are also at a moderate level. Students have been influenced by various influences such as mass media, ideologies and other social aspects. Thus, the objective of this study was to provide more information on issues in sustainable fashion education. The researcher also tried to channel some initiatives and the mechanism that can be used for the ESD practice approach in fashion education. The methodology used in this article was through the information review of previous studies. The information collected consists of articles of study and existing reports. The general and specific keywords were also used in the information search. Besides, the researcher also modified previous research results and combined various previous research findings to identify issues and trends of ESD in fashion education. From the findings, several parties play important roles in practising ESD in fashion education. The parties involved are educators, educational institutions, the government and the industry. In addition, various approaches can be done to promote ESD practices to students such as the application of mixed technology, the use of conceptual models in the fashion curriculum, the development of sustainable fashion courses, innovation in curriculum and pedagogy as well as collaborative activities between institutions and the industry. The findings also showed that several theories and models of previous studies discussed the significant relationship of factors influencing ESD practices. Those theories are Theory of Planned Behavior-TPB, Norm Activation Theory - NAT, Predictors of Environmental Behavior: PEB model and KAP Model.